Compartmentalisation of the inflammatory response following aneurysmal subarachnoid haemorrhage. (November 2019) - Al-Tamimi, Yahia Z.; Bhargava, Deepti; Orsi, Nicolas M.; Teraifi, Anmar; Cummings, Michele; Ekbote, Uma V.; Quinn, Audrey C.; Homer-Vanniasinkam, Shervanthi; Ross, Stuart
Abstract: Introduction: There is some evidence to suggest that a systemic and central nervous system (CNS) inflammatory response occurs following aneurysmal subarachnoid haemorrhage (aSAH) which may be related to the pathophysiology of early brain injury and delayed ischaemic neurological deficit (DIND). The aim of this study was to measure inflammatory mediator levels in plasma and cerebrospinal fluid (CSF) in the days following aSAH and to determine their association with aSAH, DIND and clinical outcome. Material and methods: Plasma and CSF samples were obtained prospectively from patients with aSAH on days 1–3, 5, 7 and 9 and profiled for interleukin (IL)-1α, IL-1β, IL-4, IL-6, IL-8, IL-10, IL-15, IL-17, IL-18, macrophage chemotactic protein (MCP)-1, vascular endothelial growth factor (VEGF) and tumour necrosis factor (TNF)-α. Plasma and CSF samples from non-aSAH patients undergoing spinal anaesthesia were used as controls. Results: The CSF levels of all cytokines investigated except for IL-1α were significantly higher in aSAH compared to controls in the first seven days of ictus. CSF levels of IL-1α (p = 0.014), IL-18 (p = 0.016), IL-6 (p = 0.0006) and IL-8 (p = 0.006) showed significant increases in the days following aSAH. Conversely IL-17 demonstrated a decrease. In particular, IL-4 was higher in the CSF of patients who had DIND at all time-points (p = 0.032). Plasma IL-6 and IL-8 levels were higher, and IL-1α levels lower, than controls at most time-points. All mediators demonstrated persistent elevation in the CSF compared to plasma apart from IL-1α and IL-18 which followed the opposite trend. Day 3 plasma IL-6 levels predicted poor outcome at six months (Exp(B) 1.12 1.03-1.22, P = 0.012), although this association was lost in the second analysis incorporating Fisher grade, WFNS grade and age. Conclusion: The post aSAH inflammatory response peaks on days 5–7 post ictus and remains largely compartmentalised within the CNS. IL-4 may have a particular association with DIND although its precise role in the pathophysiology of the disorder remains unclear. IL-6 predicted poor outcome but not independently of clinical grade, suggesting that it may be a surrogate marker of early brain injury.